Hadith #2230 - Sunan Ibn Majah - Anas ibn Malik; Hilal bin Jubayr /Jabar هلال بن جبير ويقال بن جبر; Muhammad bin 'Abdullah bin Qahzad محمد بن عبد الله بن قهزاد; Muhammad bin Bashar Bindar محمد بن بشار بندار (Sunan Ibn Majah)
“The neighbor has more right to property that is near.”
Grade: